Gowth Rates and Relative Contributions of Different Components towards the Production of Oil-seed Crops in Gujarat - Shiyani, R L; Jha, B K (Annals of Arid Zone, 2016)
An attempt has been made in this paper to study the compound growth rates in area, production and productivity of major oil-seeds viz. groundnut, sesamum, castor and rapeseed niustard of the Gujarat. To measure the relative contribution of area, yield and prices in increase of oilseeds production. deconiposition analysis has been carried out. The study is based on secondary data collected for the period from 1966-67 to 1989- 90. The results revealed that the product tyofg roundnut and sesaniuni remained almost stagnant in all the districts i flderstud , while the area. production and productivity of castor and rapeseed mustard increased significantly. The Kutch district was an esception in both the cases. Decon positiona nalysis revealed that thc price factor individually contributed the most to increases in the production of groundnut and sesamum, whereas tlic combination of yield. Inore area and better price gavc pokitive growth impact for castor and rapeseed-mustard.